Positive and negative viral associations in patients with acute respiratory tract infections in primary care: the ECOVIR study - Hortense Petat; Matthieu Schuers; Christophe Marguet; Xavier Humbert; François Le Bas; Andry Rabiaza; Sandrine Corbet; Bryce Leterrier; Astrid Vabret; Meriadeg Ar Gouilh (Frontiers Media S.A., 2023)
IntroductionAcute respiratory infections (ARIs) are the most common viral infections encountered in primary care settings. The identification of causal viruses is still not available in routine practice. Although new strategies of prevention are being identified, knowledge of the relationships between respiratory viruses remains limited.Materials and methodsECOVIR was a multicentric prospective study in primary care, which took place during two pre-pandemic seasons (2018-2019 and 2019-2020). Patients presenting to their General practitioner (GP) with ARIs were included, without selecting for age or clinical conditions. Viruses were detected on nasal swab samples using a multiplex Polymerase Chain Reaction test focused on 17 viruses [Respiratory Syncytial Virus-A (RSV-A), RSV-B, Rhinovirus/Enterovirus (HRV), human Metapneumovirus (hMPV), Adenovirus (ADV), Coronaviruses (CoV) HKU1, NL63, 229E, OC43, Influenza virus (H1 and H3 subtypes), Influenza virus B, Para-Influenza viruses (PIVs) 1-4, and Bocavirus (BoV)].ResultsAmong the 668 analyzed samples, 66% were positive for at least one virus, of which 7.9% were viral codetections. The viral detection was negatively associated with the age of patients. BoV, ADV, and HRV occurred more significantly in younger patients than the other viruses (p < 0.05). Codetections were significantly associated with RSV, HRV, BoV, hMPV, and ADV and not associated with influenza viruses, CoV, and PIVs. HRV and influenza viruses were negatively associated with all the viruses. Conversely, a positive association was found between ADV and BoV and between PIVs and BoV.ConclusionOur study provides additional information on the relationships between respiratory viruses, which remains limited in primary care.